2010
DOI: 10.1016/j.devcel.2009.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The Ordered Architecture of Murine Ear Epidermis Is Maintained by Progenitor Cells with Random Fate

Abstract: Typical murine epidermis has a patterned structure, seen clearly in ear skin, with regular columns of differentiated cells overlying the proliferative basal layer. It has been proposed that each column is a clonal epidermal proliferative unit maintained by a central stem cell and its transit amplifying cell progeny. An alternative hypothesis is that proliferating basal cells have random fate, the probability of generating cycling or differentiated cells being balanced so homeostasis is achieved. The stochastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
198
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(222 citation statements)
references
References 36 publications
21
198
1
Order By: Relevance
“…According to this model, epidermal homeostasis is maintained by a combination of symmetric and asymmetric cell divisions; the majority of divisions are asymmetric and progenitors divide every 6-7 d. Using the same strategy of clonal analysis, it has been proposed that the ear epidermis is also maintained by one type of progenitor that randomly chooses between two fates, although the parameters of the cell cycle and the probability to self-renew and differentiate were different (Doupe et al 2010). Although these data challenge our current view of hierarchical homeostasis, it remains to be shown that the cells targeted in these studies are not a particular subpopulation of epidermal cells.…”
Section: Stem Cells Of the Interfollicular Epidermismentioning
confidence: 99%
“…According to this model, epidermal homeostasis is maintained by a combination of symmetric and asymmetric cell divisions; the majority of divisions are asymmetric and progenitors divide every 6-7 d. Using the same strategy of clonal analysis, it has been proposed that the ear epidermis is also maintained by one type of progenitor that randomly chooses between two fates, although the parameters of the cell cycle and the probability to self-renew and differentiate were different (Doupe et al 2010). Although these data challenge our current view of hierarchical homeostasis, it remains to be shown that the cells targeted in these studies are not a particular subpopulation of epidermal cells.…”
Section: Stem Cells Of the Interfollicular Epidermismentioning
confidence: 99%
“…Later, quantitative lineage tracing studies based on inducible genetic labeling revealed that murine epidermal maintenance relies instead upon the turnover of a basal progenitor pool that conforms to a process of "population asymmetry" in which their stochastic loss through terminal division is perfectly compensated by the duplication of neighbors (27)(28)(29)(30) (Fig. 1B).…”
Section: Significancementioning
confidence: 99%
“…The resolution of cell fate behavior in mouse IFE relied upon the observation of "scaling" behavior of the clone size distribution following genetic pulse labeling (27)(28)(29)(30)35). According to their stochastic fate behavior (Fig.…”
Section: Significancementioning
confidence: 99%
“…Both tissues are maintained by single populations of functionally equivalent progenitor cells [9][10][11]13,15]. As in the intestine, progenitor cell division is linked with the migration of a nearby differentiating cell out of the basal layer.…”
Section: Neutral Competition: Stem Cells In Homeostatic Tissuementioning
confidence: 99%
“…An important insight has been that clone size distributions at multiple time points can be used to generate simple quantitative models that capture the average behaviour of proliferating cells in homeostatic tissue [6,9]. This approach has since been applied in a series of studies in the epidermis, oesophagus, and intestine [10][11][12][13][14][15]. A recent development has been in vivo video imaging techniques, which complement the long-term lineage data with direct visualization of the behaviour of individual cells over a few rounds of cell division [16,17].…”
Section: Neutral Competition: Stem Cells In Homeostatic Tissuementioning
confidence: 99%